Ai-Driven in Education Settings: Transforming Educational Landscapes for the Future - Bachtiar, Bachtiar; Nirmala, Sri Dewi; Munawir, Abdillah; Mujiono, Mujiono (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
This paper reports the outcomes of a ‘Community Service’ activity related to the integration of artificial intelligence (AI) in educational settings to enhance learning outcomes. The primary objective of the discussion activities is to equip educators with AI-driven tools to improve teaching practices and student outcomes. The initiatives were conducted in Bogor, Indonesia, involving 50 teachers from SMK-SMAK Bogor. Key aspects highlighted in the article include AI’s role in creating more inclusive and adaptive learning environments, challenges associated with its implementation in educational settings, and the critical importance of teacher training in utilizing this technology effectively. The article emphasizes how AI facilitates collaborative learning, provides real-time feedback, and supports educators in designing more efficient digital-based lesson plans. By leveraging AI, the program aims to foster a more dynamic and responsive educational environment, better-preparing students for the challenges of the digital age. The activity outcomes imply that AI integration in education can significantly improve learning equity and flexibility while promoting teacher readiness to navigate future technological advancements in pedagogy. Additionally, it offers valuable insights into overcoming barriers to AI adoption, particularly in under-resourced educational contexts.